(untitled) (Journal of the Bangladesh Chemical Society, 2012)
The electrochemical redox behavior of Cu(II) has been investigated at glassy carbon electrode (GCE) in Britton-Robinson (BR) buffer as well as in a mixture of BR buffer and potassium chloride media. It is apparent that BR buffer can act as a supporting electrolyte and modify the electrochemical behavior of Cu(II) ion in aqueous medium. In BR buffer medium, Cu(II) undergoes one two-electrons redox process, while in a mixture of BR buffer and KCl media it follows two one-electron electrochemical reaction routes. Because of the formation of hydrogen bridge bond between the supporting electrolyte and GCE surface, the Cu(II) ion follows Cu(II)/Cu(0) electrochemical reaction path, while in presence of KCl such a hydrogen bridge bond is not formed and it undergoes successive Cu(II)/Cu(I) and Cu(I)/Cu(0) electrode reaction processes. Moreover, the linear variation of peak current with the square root of scan rate indicates that the electrochemical redox processes are diffusion controlled. Keywords: Supporting electrolytes; Britton-Robinson buffer; Cu-reduction; Peak current DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9704 Journal of Bangladesh Chemical Society, Vol. 24(2), 158-164, 2011